Role of Mediator in Medan Religious Court in Reducing the Number of Divorce from 2016 to 2018 - Eko Yudhistira, Zulfi Chairi , Rosnidar Sembiring (International Journal of Advanced Science and Technology, 2020)
Every year The Religious Court of Medan has a high number of divorce case. It has been proven from the data revealed by the court. From January 2016 to June 2018, there are 7.443 divorce cases. From that number, only 19 cases can be solved through the mediation process. Mediation process is a process which will be conducted before the trial start. In this process all parties, husband and wife will be invited by the court to come and meet each other in a room. This mediation process will be facilitated by a Mediator. In this process both parties will do a discussion about their family, their problem, and their will. This process is a way which is initiated by the government to complicate the divorce process and reduce the number of divorce case. Furthermore the government hope that through this process, both parties who have had a discussion will think twice about the impact and the result of divorce, and try to solve the problem through discussion not divorce.  Mediation Process is set in the Indonesian Supreme Court Law (PERMA) Number 1 of the year 2016 about Mediation. From the fact above, there is a fact that the mediation process does not work functionally. This research will show the obstacles which are faced in the mediation process. In the other side this research will also analyze the role of Mediator in the Mediation process at The Religious Court of Medan.